Limited attention and information loss in the lab-to-farm knowledge chain: The case of Malawian agricultural extension programs - Niu, Chiyu; Ragasa, Catherine (International Food Policy Research Institute, 2017)
The International Food Policy Research Institute is leading a three-year research program to assess the state of agricultural extension and advisory services provision in Malawi in order to inform the national extension policy review and reformation of government and donor processes and programming. This research program includes a series of studies undertaken in response to a request by the Ministry of Agriculture, Irrigation and Water Development to look closely at the state of extension services provision with the intent to further strengthen the contribution of these services to food security, economic growth, and the achievement of sustainable development goals. In this paper, we assess the flow of technical advice along the knowledge chain from scientists to farmers to identify the challenges in information provision. The advancement of social network literature has fostered the lead or contact farmer modality or farmer-to-farmer approach of information transmission. However, there is limited evidence regarding the information efficiency of this modality, and the reasons of the potential information loss. In this article, we assess information efficiency along the knowledge transmission chain from researchers to agricultural extension agents (EAs) to lead farmers (LFs) to other farmers. By asking the same set of questions about a fairly well known technology, pit planting, we construct a measure of knowledge at each node of the knowledge transmission chain. Descriptive evidence shows that the majority of information loss happens at the EA-to-LF link, and that the loss is potentially caused by limited attention of both EAs and LFs to all important details of the technology. With more evidence about the importance of knowledge for technology adoption, we suggest that EAs emphasize all crucial dimensions of an agricultural technique during demonstrations and visits in order to reduce information loss.